STUDI EKSPERIMENTAL NATURAL REFIGERANT DENGAN VARIASI DIAMETER TiT-HEAT EXCHANGER TERHADAP REFRIGERATOR PERFORMANCE - Ariyano; Apri Wiyono; Rifqi Rahmadiansyah; Rani Anggrainy; Dibyo Setiawan; Zeqy Zulhaqy (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
ABSTRACT Almost all households in Indonesia use a refrigerator as a place to store food that is more durable. But behind these needs, refrigerators are identified as one of the household appliances that use high electrical energy. Therefore, this study aims to examine the use of Tube in Tube Heat Exchanger (TiTHX) with refrigerant R290 in the refrigerator system to reduce household electricity consumption. This research was conducted experimentally by varying the 3 diameter ratios on TiTHX. The results showed that the use of TiTHX with the most optimum value was obtained at the variation diameter ¼ : ½ increasing refrigerator performance by 3.7%. and also reduce the consumption of electricity costs up to Rp. 17,544.44 per month. This is because the difference between the evaporation pressure and condensation pressure is smaller in systems using TiTHX which then results in lower compression work.